Steroidal antiinflammatory drugs: glucocorticoids - Sônia Maria Alvarenga Anti; Rina Dalva Neubarth Giorgi; Wiliam Habib Chahade (Einstein (São Paulo), 2008)
Glucocorticoids are largely used drugs because of theirimmunosuppressive and anti-infl ammatory effects in the treatment ofmany rheumatic and other infl ammatory diseases. However, their useis sometimes limited by numerous adverse reactions. In this chapterphysiologic and pharmacological aspects as well as their mechanismof action and administration are presented. The use of glucocorticoidsin old age is specially discussed. Drug interaction and adverse effectsare also reviewed.